PENGUATAN PRODUK “EII BANDENG PRESTO” MELALUI STRATEGI BRANDING - Berlianingsih Kusumawati; Yanti Budiasih; Siti Maryama (Jurnal Abditani, 2021)
Tangerang City is one of the cities that has high concern in creating new entrepreneurs. As a city of MSMEs, South Tangerang City needs to increase its superior products which are characteristic of regional products. Among the entrepreneurs who have great potential to be developed and become an icon for the city of South Tangerang are Presto Milkfish processed products. However, this small industry still has obstacles, making it difficult to develop. With regard to the problems faced, the objectives of this activity are (1) To provide assistance and training in branding the EII Bandeng Presto products; (2) Provide assistance in an effort to make the EII Bandeng Presto product a superior product and a characteristic product of South Tangerang City; (3) Providing marketing assistance in order to reach a wider market. The method of activities to be carried out is a participatory approach through three stages, namely, preliminary surveys, mentoring, and evaluation. Activities to produce good and attractive partner product packaging. The results of the packaging evaluation show that the packaging used is quite good and attractive according to the packaging function.